Efektivitas Perkuliahan Munazarah Untuk Meningkatkan Kemampuan Berbicara - Jannah, Miftahull; Suyudi, Ahmad; Perdana, imannudin Sendi; Septian, Nyanyang; Ghibran, Alfin Khalil; Putri, Arisna Rukmana (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Education plays an important role in creating a learning atmosphere and learning process that is needed by every human being. One of the skills that must be possessed by students is speaking skill. This study aims to analyze the effect of applying the munazarah method on the speaking skills of Arabic language education study program students at the Muhammadiyah University of Yogyakarta (UMY) in the munazarah course. Where from the results of observations the researchers saw that the students of Yogyakarta Muhammadiyah University seemed to really master Arabic well. The data collection techniques and tools used in this study were interviews and direct observation. Based on the research results, it can be concluded the following things. The results of their interviews stated that before entering semester 2, where there was no munazarah course to be precise, they were not very good at mastering Arabic speaking skills. As a result of their own expressions when there is reflection and training at each meeting, their Arabic speaking skills in this munazarah course are increasing in semester 5 so that they can implement it through speeches, poetry and even compose and compose Arabic texts by themselves.